Managing Acute Catatonia with Intramuscular Midazolam: Expanding the Therapeutic Toolkit - Emerick, Gustavo Correa; Mafredi, Mariana; Mattos, Vicente Gabriel Winck; Siqueira, Ana Caroline Alencar (Brazilian Journal of Case Reports, 2026)
According to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5 TR), catatonia is a behavioral syndrome characterized by psychomotor disturbances that, despite the individual’s full physical capacity to perform movements, become abnormal (limited, excessive, or eccentric movements). It is a serious condition that requires immediate treatment, aiming for complete remission. Management involves multidisciplinary measures, such as monitoring water/food intake, preventing deep vein thrombosis (DVT) and pulmonary embolism (PE), contractures and pressure ulcers, and controlling psychomotor activity. Catatonia is treated with benzodiazepines (especially oral or intramuscular lorazepam) or electroconvulsive therapy (when resistant to drug treatment). This objective report presents the case of an 18-year-old patient who presented her first catatonic episode during a psychiatric hospitalization, with negativity/resistance to oral treatment. The patient presented rapid resolution (approximately 15 minutes) after the administration of 5 mg of intramuscular midazolam. This choice was attributed to the unavailability of first-line treatment (lorazepam) at the facility, in addition to the negativistic symptoms that prevented oral administration. The Bush-Francis Catatonia Rating Scale (BFCRS) was administered before and after treatment, increasing the score from 33 to 12, resolving some signs/symptoms of the catatonic episode: stupor, catalepsy, cerebral floppiness, mutism, negativity, mannerism, stereotypies, and grimaces. This allowed continued oral treatment. Midazolam may be a good, rapid, and safe option in these specific cases where other psychotropic drugs are unavailable. This is one of the few cases in which this measure has been used in a clinical context. Further studies are needed to investigate and support the basis of this therapeutic option. The patient was recruited through an active search and was fully informed, along with his or her legal guardian, about all aspects of the study, including its objectives, procedures, potential risks, and benefits. Express consent was obtained by signing the Informed Consent Form (IC), amended in accordance with current ethical guidelines.